How many ladders of investment? - Fernando Herrera-González (International Telecommunications Society (ITS), 2011)
The ladder of investment is a regulatory approach that has been used by European National Regulatory Authorities (NRAs), in order to foster infrastructure competition among operators. the idea is to force incumbent operators to open several levels of access to their network in such a way that alternative operators may climb up the ladder, using more of his own infrastructure, and thus decreasing their reliance on the wholesale products of the incumbent operator. In order to market their own services, the alternative operator has to complement the wholesale resources acquired from the incumbent operator in regulated conditions. In principle, these complementary resources should be acquired in commercial conditions, but this is not always the case. For example, the alternative operator may use some physical space in the incumbent's premises to deploy their equipment, or rely on capacity services delivered by the incumbent operator in regulated conditions in order to reach specific geographical points. This suggests that analysing the degree of advance just in the main ladder of investment could suppose a gross underestimation of the reals degree of alternative infrastructure deployment by alternative operators. In this paper, we provide a theoretical explanation for this phenomenon with the help of the theory of the discovery market process and the theory of capital, as proposed by the Austrian School of Economics. The situation of the identified ladders of investment is assessed for the Spanish market, and some conclusions are drawn and applied in the form of policy recommendations for the NGN ladder of investment.
Keywords: B53; K23; L43; L51; L96; 330; Austrian School of Economics; discovery market process; complementarity; ladder of investment; capital structure; NGN